Ordinance No. 3, § 1, Washougal Town Council (1908) (Washougal, Washington). - (:unkn) unknown (My University, 1909)
All persons (except police officers and other persons whose duty it is to execute process or warrants or make arrests] who shall carry upon his or her person any concealed weapon consisting of a revolver, pistol or other firearms or any knife (other than an ordinary pocket knife) or any dirk or dagger, sling shot or metal knuckles, or any instrument by use of which injury could be inflicted upon the person or property of any other person in said town. And, all persons (except police officers as aforesaid and persons practicing at shooting in a shooting gallery duly licensed) who shall, within the town limits, fire off or discharge any gun, pistol or firearm of any kind, or any bomb, shall be deemed and are disorderly persons and guilty of a misdemeanor
Keywords: CARRY - CONCEALED; DISCHARGE